Evaluating Relative Heat Stress in Natura 2000 Site Kras in Different Climate Change Scenarios - A Case Study Utilizing Multiscale Geographically Weighted Regression - Davidovič, Danijel; Ivajnšič, Danijel (Journal for Geography, 2024)
The study evaluates relative heat stress in the Natura 2000 site Kras under various climate change scenarios using Multiscale Geographically Weighted Regression (MGWR). Kras, a limestone plateau in southwestern Slovenia, is highly vulnerable to droughts and wildfires due to its high insolation. Optical and thermal satellite imagery and five future air temperature scenarios were utilized to downscale thermal conditions and evaluate relative heat stress in the study area. Results indicate significant spatio-temporal variability in LST, with the southeastern region being particularly susceptible to elevated heat stress. Projections show an overall increase in heat stress due to climate change, with potential reductions in densely vegetated areas. The study emphasizes the need for spatially explicit analyses and adaptive strategies to mitigate heat stress impacts on ecosystems and human populations.